THE INFLUENCE OF THE STORE AS SPATIAL SETTING TOWARD THE MAIN CHARACTER’S DEVELOPMENT IN SAYAKA MURATA’S CONVENIENCE STORE WOMAN - Chotib, Mochamad Nasrul; Syahnia, Sherinkeshia Usagi Arneta; Widodo, Herditya Wahyu (J-ELLiT (Journal of English Language, Literature, and Teaching), 2023)
This research examines Keiko Furukura’s character development influenced by the convenience store as the main spatial setting in Sayaka Murata’s novel entitled Convenience Store Woman (2018). The study is a literary criticism which uses the theory of New Criticism, especially its argument that centers on the analysis of the main character in the story. This research proposes that spatial settings can become one of most determinant factors to affect the character’s development in the story. The finding proves that the store is influential to the main character’s development as it plays as the character’s life-anchor to evaluate, measure or even, eventually, decide how worthy the main character is as a human.